A Study on Cryogenic Supercritical Carbon Dioxide Coolant Delivery Technique when Machining of AISI 1045 Steel / Erween Abd Rahim ...[et al.] - Abd Rahim, Erween; Jaafar, Mohd Noor; Mohid, Zazuli; Ibrahim, Mohd Rasidi; Ahmad, Said (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
The machining operation involves a material removal process and develop high temperature due to the friction force. The heat generated at the region of cutting edge has critical influences on machining process. It can increase cutting tool wear, reduce tool life, get rise to thermal deformation and might consequence to microcracks. The application of cutting fluid at the cutting zone by conventional process could overcomes the aforementioned problems to some extent via cooling and lubrication process. However, the waste of cutting fluid might be profuse and its impact on the environment. A new efficient process, cryogenic cooling using carbon dioxide gas (CO2) has been introduced on improving the cooling process. This technique is more economical in coolant usage while maintaining significant performance including cutting temperature, cutting force and surface roughness. The pulse mode of CO2 cooling spray under supercritical state has been used to corroborate the machining process by reducing the cutting zone temperature as to reducing coolant usage.